Pengaruh Work-Life Balance, Loyalitas Kerja Dan Komitmen Organisasi Terhadap Organizational Citizenship Behavior Di Grand Mercure Medan Angkasa Hotel - Tahniah, Diba Putri; Hafizah; Ritonga, Ilham Mubaraq (Yayasan Cita Cendekiawan Al Khwarizmi, 2022)
This study aims to determine whether work-life balance, work loyality and organizational commitment affect organizational citizenship behavior at Grand Mercure Medan Angkasa Hotel. Multiple linear regression analysis research design is used to determine how the influence between the independent variable and the dependent variable. In this research is used in associative. The population in this study were 115 employees. The sample in this study used a saturated sample, therefore the sample of this study was 115 employees which included all employees at Grand Mercure Medan Angkasa Hotel.The results of this study indicate that the ork-life Balance variable is positive and has a significant effect on Organizational Citizenship Behavior, the work loyalty variable has no significant effect on Organizational Citizenship Behavior and the Organizational commitment variable has no significant effect on Organizational Citizenship Bihavior.